Lithium ion battery

By doping Ni or Mn elements into the positive electrode material of the lithium-ion battery and adding specific additives to the non-aqueous electrolyte to form a stable interface film, the problem of unstable structure of the positive electrode material after the lithium-ion battery is increased is solved, and the effect of suppressing impedance growth and extending battery life is achieved.

CN119627230AActive Publication Date: 2025-03-14SHENZHEN CAPCHEM TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510093676.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-14
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

After the cutoff voltage is increased, the structure of the positive electrode material is unstable, resulting in a decrease in battery life, and a single improvement measure is often unsatisfactory.

Method used

A lithium cobalt oxide positive electrode material containing at least one metal element in Ni or Mn is used, and a specific proportion of the first additive and the second additive, including nitrile compounds, are added to the nonaqueous electrolyte to form a stable interface film to inhibit impedance growth.

Benefits of technology

By improving the stability of the cathode material and the compatibility of the electrolyte, it suppresses impedance growth during high-temperature cycles and storage processes, extends battery life and improves electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005252278900000021
    Figure BDA0005252278900000021
  • Figure BDA0005252278900000071
    Figure BDA0005252278900000071
  • Figure BDA0005252278900000072
    Figure BDA0005252278900000072
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a lithium ion battery which comprises a positive pole piece, a negative pole piece and a non-aqueous electrolyte, the positive pole piece comprises a positive pole material layer containing a positive pole active material, and the positive pole active material comprises lithium cobalt oxide containing at least one metal element of Ni or Mn; the non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive; the additives comprise at least one first additive selected from the following compounds and a second additive selected from nitrile compounds; the lithium ion battery satisfies the following conditions: 3 < = b + c < = 8, 0.03 < = b / c < = 0.6, 2 < = a / c < = 1500, 10 < = a < = 5000, 0.1 < = b < = 2, and 2.5 < = c < = 6.5. According to the invention, dissolution of positive electrode Co < 4 + > can be greatly reduced, stable interfacial films are formed on the surfaces of positive and negative electrodes, and the stability of the positive electrode material is improved; meanwhile, the first additive and the second additive are cooperatively used, cobalt ions dissolved out of the positive electrode can be complexed, the overall stability of the battery is further improved, and impedance increase in the high-temperature storage and circulation process is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery capable of suppressing impedance growth. Background Art

[0002] Compared with traditional batteries (such as nickel-cadmium batteries and nickel-metal hydride batteries), lithium-ion batteries have significant advantages such as high energy density, strong fast charging capability, and high operating voltage, making lithium-ion batteries increasingly widely used in modern consumer electronic devices and electric vehicles.

[0003] With the continuous upgrading trend of consumer electronic products, the performance requirements of lithium-ion batteries for thinness and durability are more stringent. In order to meet the growing performance requirements, the current strategy of increasing the cut-off voltage is mainly adopted to increase the energy density of the battery. However, the increase in the cut-off voltage will cause the instability of the positive electrode material structure, which will in turn cause problems such as reduced battery life, thus affecting the practical application of high-voltage lithium cobalt oxide. At present, the method for optimizing the electrochemical properties of lithium cobalt oxide positive electrode materials can be achieved from the material itself by modifying the material, such as using surface coating or bulk doping to modify the material to improve the battery performance of lithium cobalt oxide batteries under high voltage conditions. However, the improvement of a single condition is often unsatisfactory. Generally speaking, the battery structure includes a positive electrode, a negative electrode, a separator and an electrolyte. As the "blood" of the battery, the electrolyte is the carrier of ion transmission in the battery. It plays the role of conducting lithium ions between the positive and negative electrodes, providing an environment for lithium ions to be freely deintercalated, and has an important influence on the energy density, specific capacity, operating temperature range, cycle life, safety performance, etc. of lithium-ion batteries. By adding appropriate electrolyte additives to the electrolyte, the positive electrode material can be stabilized and the performance of the battery can be further improved. Therefore, it is necessary to consider the positive electrode material and the electrolyte comprehensively in order to obtain the best battery performance. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a lithium ion battery with excellent impedance growth inhibition effect.

[0005] The present invention adopts the following technical solutions:

[0006] A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, and a non-aqueous electrolyte;

[0007] The positive electrode plate includes a positive electrode material layer containing a positive electrode active material, wherein the positive electrode active material includes lithium cobalt oxide containing at least one metal element of Ni or Mn;

[0008] The non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive;

[0009] The additives include a first additive and a second additive, wherein the first additive includes at least one of the following compounds:

[0010]

[0011] The second additive includes a nitrile compound;

[0012] The lithium-ion battery meets the following conditions:

[0013] 3≤b+c≤8, 0.03≤b / c≤0.6, 2≤a / c≤1500, 10≤a≤5000, 0.1≤b≤2, 2.5≤c≤6.5;

[0014] Wherein, a is the total content of Ni and Mn elements in the positive electrode material layer, in ppm;

[0015] b% is the mass percentage of the first additive in the non-aqueous electrolyte, in %;

[0016] c% is the mass percentage of the second additive in the non-aqueous electrolyte, in %.

[0017] The lithium ion battery of the present invention is based on improving the stability of the lithium cobalt oxide positive electrode active material, and the lithium cobalt oxide positive electrode active material contains at least one metal element of Ni or Mn; based on the compatibility of the non-aqueous electrolyte with the positive and negative electrode materials, at least one of the following compounds is used as the first additive in the non-aqueous electrolyte, and a nitrile compound is used as the second additive; after a lot of research, the inventor found that when the relationship between the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage b of the first additive in the non-aqueous electrolyte, and the mass percentage c of the second additive in the non-aqueous electrolyte satisfies 3≤b+c≤8, 0.03≤b / c≤0.6, 2≤a / c≤1500, 10≤a≤5000, 0.1≤b≤2, 2.5≤c≤6.5, the stability of the battery positive electrode active material can be improved, and the impedance growth during high temperature cycling and storage can be suppressed. It is speculated that by doping or coating Ni or Mn elements in lithium cobalt oxide, the LCO structure can be regulated at the atomic scale, which is beneficial to enhance the structural stability under high voltage, greatly reduce the dissolution of cobalt ions in the positive electrode, and improve the electrochemical performance; at the same time, by controlling the relationship between the total content of Ni and Mn elements in the positive electrode material layer and the first additive, the first additive is ensured to form a uniform film on the positive electrode surface, further reducing the increase in impedance during the cycle process; the synergistic effect of the first additive and the second additive can produce a stable interface film at the interface between the positive and negative electrodes and the electrolyte, thereby reducing the impedance growth during battery operation.

[0018] Ni or Mn elements can be added to the lithium cobalt oxide positive electrode active material by doping. Ni or Mn can be embedded in the lattice of lithium cobalt oxide, replacing part of the cobalt position, forming a stable doping state, and inhibiting the dissolution of Co ions; Ni or Mn elements are also coated on the outer surface of lithium cobalt oxide in the form of Ni or Mn oxides to avoid direct contact between the positive electrode active material and the non-aqueous electrolyte, thereby inhibiting the dissolution of Co ions. Using at least one metal element of Ni or Mn as a doping or coating element, compared with elements such as Mg, Al, Zr, W, F, B, Cr, Mo and rare earth elements, within a certain range, Ni elements can improve the material activity of lithium cobalt oxide positive electrode and reduce the phenomenon of cation mixing, while Mn elements can delay the phase change of lithium cobalt oxide positive electrode materials under high voltage, thereby improving the electrochemical properties of lithium cobalt oxide positive electrode materials and maintaining good structural stability under high voltage.

[0019] The positive electrode active material contains Ni or Mn, which may be dissolved into the electrolyte during battery storage or circulation, thereby deteriorating battery performance. By adding the second additive and controlling the total content of Ni and Mn elements and the content of the second additive to be between 2≤a / c≤1500, the second additive can complex a small amount of dissolved nickel and manganese ions to avoid the negative impact of the introduced metal elements on battery performance. Preferably, the total content of Ni and Mn elements and the content of the second additive are between 12.5≤a / c≤750.

[0020] In the non-aqueous electrolyte of the present invention, when the first additive and the second additive are used simultaneously and the content relationship thereof satisfies 3≤b+c≤8 and 0.03≤b / c≤0.6, a synergistic effect can be formed, and an interface film with good conductivity, suitable mechanical strength and strong stability is generated at the interface between the positive and negative electrodes and the electrolyte. The presence of the excellent interface film can inhibit the side reactions of the electrolyte at the positive and negative electrodes, and the presence of the two additives can also complex the transition metal ions dissolved from the positive electrode, thereby protecting the stability of the structure of the positive electrode active material and reducing the impedance growth during the operation of the battery. When the total content of the first additive and the second additive is less than 3%, the quality of the positive and negative electrode interface film will be affected, and the transition metal ions dissolved from the positive electrode will not be effectively complexed, the protection of the positive and negative electrodes is limited, and it is difficult to significantly improve the stability of the material; when the total content of the first additive and the second additive is greater than 8%, a thicker interface film is formed at the positive and negative electrodes, resulting in an increase in the impedance of the positive and negative electrode interfaces, thereby affecting the battery performance. When the content ratio of the first additive to the second additive is less than 0.03 or greater than 0.6, the two cannot play a synergistic role, which will lead to excessive battery impedance, thereby causing battery performance degradation. Preferably, the content relationship between the first additive and the second additive satisfies 3.5≤b+c≤7, 0.05≤b / c≤0.5.

[0021] Specifically, in some embodiments of the present invention, by coating or doping at least one metal element of Ni or Mn with a content of 10 to 5000 ppm in the lithium cobalt oxide positive electrode active material, the coated or doped nickel and manganese elements can occupy the Li, Co and O lattice sites in the LCO lattice, thereby regulating the structure of LCO at the atomic scale, which is beneficial to enhancing the structural stability under high voltage, including inhibiting irreversible phase change and reducing strain / stress, reducing redox to stabilize the particle phase and surface structure, and expanding the interlayer spacing to enhance Li + Diffusion, greatly reducing the positive electrode Co 4+ If the amount of Ni and / or Mn introduced is too low, the stability of the lithium cobalt oxide positive electrode will not be improved; if the amount of Ni and / or Mn introduced is too high, the layered structure of the lithium cobalt oxide will be destroyed, and microcracks and surface side reactions will be promoted. More specifically, the total content a of Ni and Mn elements in the positive electrode material layer is 10ppm, 30ppm, 50ppm, 100ppm, 200ppm, 500ppm, 600ppm, 800ppm, 1000ppm, 1200ppm, 1500ppm, 1800ppm, 2000ppm, 2200ppm, 2400ppm, 2500ppm, 2800ppm, 3000ppm, 3200ppm, 3500ppm, 3800ppm, 4000ppm, 4200ppm, 4500ppm, 4800ppm, 5000ppm or a range composed of any two of these values; preferably, the total content of Ni and Mn elements in the positive electrode material layer is 100-3000ppm; more preferably, the total content of Ni and Mn elements in the positive electrode material layer is 200-1000ppm.

[0022] Specifically, in some embodiments of the present invention, at least one of compounds 1-5 is used as the first additive, which can form a film on the positive and negative electrodes at the same time, and has an excellent protective effect on the positive and negative electrode materials, thereby improving the stability of the positive and negative electrode materials, inhibiting the high temperature storage and cycle impedance growth of the battery, and also having a good inhibitory effect on the gas production of the battery during high temperature storage. More specifically, the mass percentage b% of the first additive is 0.1%, 0.2%, 0.3%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.3%, 1.5%, 1.6%, 1.8%, 2% or a range consisting of any two of these values; preferably, the mass percentage b% of the first additive is 0.3-1.5%.

[0023] Specifically, in some embodiments of the present invention, a nitrile compound is used as the second additive, and the nitrile compound contains a cyano group or a cyano group, which can form a stable interface film on the surface of the positive electrode material. Thereby inhibiting the decomposition of the electrolyte and the dissolution of cobalt ions, maintaining the structural integrity of the lithium cobalt oxide positive electrode active material, thereby inhibiting the increase of the interface impedance and improving the overall electrochemical performance of the battery. More specifically, the mass percentage c% of the second additive is 2.5%, 2.7%, 2.8%, 3%, 3.2%, 3.5%, 3.6%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.8%, 6%, 6.2%, 6.3%, 6.5% or a range consisting of any two of these values; preferably, the mass percentage c% of the second additive in the non-aqueous electrolyte is 4 to 6%.

[0024] Specifically, in some embodiments of the present invention, the nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacate.

[0025] Specifically, in some embodiments of the present invention, increasing the porosity of the positive electrode material layer can increase the contact area between the positive electrode active material and the electrolyte, which is beneficial to the transmission of lithium ions, thereby improving the battery performance; however, if the porosity is too large, the contact impedance will also increase, and the internal connectivity may also deteriorate during the battery cycle, increasing the transmission path length of electrons and ions, thereby increasing the internal resistance and cycle impedance of the battery; therefore, the present invention controls the porosity ε% of the positive electrode material layer to 10-40%, which helps to improve the ion conduction rate and slow down the continuous growth of the uneven interface film, thereby slowing down the increase in impedance during the cycle. More specifically, the porosity of the positive electrode material layer is 10%, 12%, 13%, 15%, 18%, 20%, 21%, 24%, 25%, 27%, 28%, 30%, 32%, 35%, 37%, 40% or a range consisting of any two of these values; preferably, the porosity ε of the positive electrode material layer is 13-30%.

[0026] Specifically, in some embodiments of the present invention, the content of the first additive and the porosity of the positive electrode material layer are limited, and the content b% of the first additive and the porosity ε% of the positive electrode material layer are controlled to be between 0.01≤b / ε≤0.2, which can ensure that the first additive is uniformly filmed on the positive electrode surface, thereby reducing the increase in impedance during the cycle. Preferably, the content b% of the first additive and the porosity ε% of the positive electrode material layer are between 0.01≤b / ε≤0.15.

[0027] Specifically, in some embodiments of the present invention, the non-aqueous electrolyte further includes a third additive, and the third additive includes at least one of fluorobenzene, 1,3,5-trifluorobenzene, 1,4-difluorobenzene, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether. The mass percentage d% of the third additive in the non-aqueous electrolyte is 1 to 10%. The molecular structure of the third additive contains fluorine atoms, which have strong electronegativity and small atomic radius, which makes the third additive containing fluorine atoms show strong polarity and low surface tension, which helps to reduce the surface tension of the electrolyte at the positive and negative electrode interfaces, so that the electrolyte can better wet the electrode surface and reduce the interface impedance. More specifically, the mass percentage d% of the third additive is 1%, 2%, 3%, 5%, 7%, 8%, 9%, 10% or a range composed of any two of these values; preferably, the mass percentage d% of the third additive is 1 to 5%.

[0028] Specifically, in some embodiments of the present invention, the mass percentage b of the first additive, the mass percentage c of the second additive, and the mass percentage d of the third additive satisfy 0.1≤d / (b+c)≤2.5. The fluorine-containing third additive helps to improve the wettability of the electrolyte to the positive and negative electrodes under high energy density. The introduction of the first additive and the second additive will increase the viscosity of the electrolyte and reduce the fluidity of the electrolyte, which is not conducive to improving the initial impedance of the battery under high energy density. By using the third additive in combination and limiting the content relationship between the three, it helps to reduce the initial impedance of the electrolyte and increase the liquid retention, thereby improving the electrochemical performance of the battery. Preferably, the mass percentage b of the first additive, the mass percentage c of the second additive, and the mass percentage d of the third additive satisfy 0.2≤d / (b+c)≤1.5.

[0029] Specifically, in some embodiments of the present invention, the organic solvent includes at least one of a cyclic carbonate solvent, a linear carbonate solvent, a carboxylate solvent, and an ether solvent.

[0030] In some preferred embodiments, the cyclic carbonate solvent includes at least one of ethylene carbonate, propylene carbonate, fluoroethylene carbonate, vinylene carbonate and butylene carbonate.

[0031] In some preferred embodiments, the linear carbonate solvent includes at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate.

[0032] In some preferred embodiments, the carboxylate solvent includes at least one of ethyl acetate, ethyl propionate, propyl propionate, ethyl difluoroacetate, methyl acetate, methyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate and ethyl trimethylacetate.

[0033] In some preferred embodiments, the ether solvent includes at least one of ethylene glycol dimethyl ether, 1,3-dioxolane and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0034] Specifically, in some embodiments of the present invention, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide salts.

[0035] Specifically, in some embodiments of the present invention, the additive further includes an auxiliary additive, and the auxiliary additive includes at least one of cyclic sulfate compounds, sultone compounds, cyclic carbonate compounds, phosphate compounds and borate compounds.

[0036] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.

[0037] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.

[0038] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 1:

[0039]

[0040] In the structural formula 1 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group;

[0041] In some preferred embodiments, the compound represented by structural formula 1 includes at least one of the compounds represented by compounds 1-1 to 1-6 below:

[0042]

[0043] In some preferred embodiments, the phosphate compound includes at least one of tris(trimethylsilyl)phosphate and a compound represented by the following structural formula 2:

[0044]

[0045] In the structural formula 2, R 31 , R 32 , R 33 Each independently selected from a saturated hydrocarbon group, an unsaturated hydrocarbon group, and a halogenated hydrocarbon group of C1-C5; more preferably, the compound shown in structural formula 2 includes at least one of triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.

[0046] In some preferred embodiments, the borate ester compound is selected from tris(trimethylsilyl)borate.

[0047] In some embodiments, based on the total mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01% to 10%. Preferably, the content is 0.1% to 5%; more preferably, the content is 0.1% to 2%. Specifically, the content of any one of the optional substances in the auxiliary additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5% or a range consisting of any two of these values.

[0048] Specifically, in some embodiments of the present invention, the positive electrode plate further includes a positive electrode binder and a positive electrode conductor. The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a thermoplastic resin such as thermoplastic polyimide, polyethylene and polypropylene; an acrylic resin; and one or more of styrene butadiene rubber. The positive electrode conductor includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene, or reduced graphene oxide.

[0049] Specifically, in some embodiments of the present invention, the positive electrode further comprises a positive electrode current collector, and the positive electrode material layer is disposed on the surface of the positive electrode current collector. The positive electrode current collector comprises a metal material that can conduct electrons, and preferably, the positive electrode current collector comprises one or more of aluminum, nickel, tin, copper, and stainless steel.

[0050] Specifically, in some embodiments of the present invention, the preparation method of the positive electrode sheet is: the positive electrode active material, the conductive agent and the binder are mixed according to the mass ratio, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, and after drying, rolling and vacuum drying, an aluminum lead wire is welded with an ultrasonic welder to obtain a positive electrode plate.

[0051] Porosity of the cathode material layer

[0052] Among them, ρ coat represents the coating volume density, ω represents the mass percentage of the coating component, ρ represents the true density of the coating component, and the subscripts AM, CA, and B represent the positive electrode active material, conductive agent, and binder, respectively.

[0053] Specifically, in some embodiments of the present invention, the negative electrode plate includes a negative electrode material layer containing a negative electrode active material, and the negative electrode active material is any one or more of a silicon-based material and a carbon material. The silicon-based material is selected from one or more of a silicon material, a silicon oxide material, a silicon-carbon material and a silicon alloy material; preferably, the silicon material is a nano-silicon material; preferably, the silicon oxide material is a SiOx material, wherein 0≤x<2; preferably, the silicon-carbon material is: a silicon-based material containing silicon and carbon materials, and / or a silicon-based material containing SiOy and carbon materials, wherein 0≤y<2; preferably, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material. The carbon material is selected from one or more of artificial graphite, natural graphite, composite graphite, graphene, and hard carbon; preferably, the carbon material is an artificial graphite material.

[0054] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder, a negative electrode conductor and a negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail here. The negative electrode binder and the negative electrode conductor may be the same as the positive electrode binder and the positive electrode conductor, respectively, which will not be described in detail here.

[0055] Specifically, in some embodiments of the present invention, the lithium-ion battery further includes a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode.

[0056] The diaphragm may be an existing conventional diaphragm, which may be a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, an inorganic-organic composite diaphragm, etc., including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP and triple-layer PP / PE / PP diaphragms.

[0057] The lithium ion battery of the present invention adopts lithium cobalt oxide as the positive electrode active material and contains at least one metal element of Ni or Mn, and adopts at least one of the following compounds as the first additive and the nitrile compound as the second additive, and defines that the relationship between the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage content b of the first additive in the non-aqueous electrolyte, and the mass percentage content c of the second additive in the non-aqueous electrolyte satisfies 3≤b+c≤8, 0.03≤b / c≤0.6, 2≤a / c≤1500, 10≤a≤5000, 0.1≤b≤2, 2.5≤c≤6.5, which can greatly reduce the positive electrode Co 4+ The dissolution of cobalt ions from the positive electrode can be prevented and a stable interface film can be formed on the surface of the positive and negative electrodes, further improving the stability of the positive electrode material. At the same time, the coordinated use of the first additive and the second additive can also complex the cobalt ions dissolved from the positive electrode, further improving the overall stability of the battery and greatly reducing the impedance growth during high-temperature storage and cycling. DETAILED DESCRIPTION

[0058] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0059] Example 1

[0060] The method for preparing a lithium-ion battery in this embodiment comprises the following steps:

[0061] 1) Preparation of positive electrode sheet:

[0062] The positive electrode active material LiCoO2 doped with Ni element, the conductive carbon black Super-P and the binder polyvinylidene fluoride (PVDF) are mixed uniformly in a mass ratio of 93:4:3, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry is evenly coated on both sides of the aluminum foil, dried, rolled and vacuum dried, and welded with an ultrasonic welder to obtain a positive electrode sheet. The porosity of the positive electrode material layer is 27%, and the content of Ni doped in the positive electrode material layer is shown in Table 1.

[0063] 2) Preparation of negative electrode sheet:

[0064] The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 94:1:2.5:2.5, and then dispersed in deionized water to obtain a negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled and vacuum dried, and a nickel lead wire was welded with an ultrasonic welder to obtain a negative electrode sheet.

[0065] 3) Preparation of electrolyte:

[0066] Ethylene carbonate (EC), diethyl carbonate (DEC) and propyl propionate (PP) are mixed in a mass ratio of EC:DEC:PP=1:1:1, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1 mol / L, and then a first additive compound 1 with a content of 0.5% and a second additive succinonitrile with a content of 3% are added.

[0067] 4) Preparation of battery cells:

[0068] A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 75°C for 48 hours to obtain a battery cell to be injected with liquid.

[0069] 5) Battery filling and formation

[0070] In a glove box with a dew point controlled below -40°C, the prepared electrolyte was injected into the battery cell, vacuum-sealed, and left to stand for 24 hours. Then, the conventional formation of the first charge was carried out according to the following steps: 0.05C constant current charging for 180 minutes, 0.2C constant current charging to 3.95V, secondary vacuum sealing, and then further 0.2C constant current charging to 4.5V, after standing at room temperature for 24 hours, 0.2C constant current discharge to 3.0V.

[0071] Examples 2-57 and Comparative Examples 1-22

[0072] This embodiment and comparative example are used to compare and illustrate the lithium-ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the differences are: the composition and content of the additive in the non-aqueous electrolyte, the type and content of the doping element in the positive electrode material layer, and the porosity of the positive electrode sheet, as shown in Tables 1-6 respectively.

[0073] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests as follows:

[0074] 1. High temperature storage performance test

[0075] The formed battery is charged at room temperature at a constant current of 1C to the cut-off voltage, then charged at constant current and constant voltage until the current drops to 0.05C, then discharged at a constant current of 1C to 3.0V, then charged to full charge and stored in an environment of 60℃ for 30 days, and then discharged at 1C to 3V.

[0076] Battery impedance growth rate after high-temperature storage (%) = [(internal resistance after 30 days of storage - internal resistance before storage) / internal resistance before storage] × 100%.

[0077] Battery capacity retention rate after high-temperature storage (%) = [(battery capacity after storage for 30 days - capacity before storage) / capacity before storage] × 100%.

[0078] 2. High temperature cycle performance test

[0079] The battery was placed in a high-temperature oven at a constant temperature of 45°C, charged at a constant current of 0.5C to the cut-off voltage, then charged at a constant voltage until the current dropped to 0.02C. After standing for 5 minutes, it was discharged at a constant current of 1C to 3.0V. This was the first cycle. 500 cycles of charge / discharge were performed under the above conditions, and the impedance growth rate and cycle capacity retention rate of the battery after 500 cycles at 45°C were calculated.

[0080] Battery impedance growth rate after cycling (%) = [(internal resistance after corresponding number of cycles - internal resistance after first cycle) / internal resistance after first cycle] × 100%.

[0081] Cycle capacity retention rate (%) = [(capacity after corresponding number of cycles - capacity after first cycle) / capacity after first cycle] × 100%.

[0082] Test Results

[0083] Table 1 shows the test results of Examples 1-22 and Comparative Examples 1-18; the differences between Examples 2-22 and Comparative Examples 1-18 and Example 1 are the relevant parameters in Table 1.

[0084] Table 1

[0085]

[0086]

[0087]

[0088] It can be seen from the test results of Examples 1-22 and Comparative Examples 1-18 that the lithium ion battery of the present invention uses lithium cobalt oxide as the positive electrode active material, and by doping at least one metal element of Ni or Mn, at least one of the following compounds and a nitrile compound are used as additives in the non-aqueous electrolyte, and the relationship between the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage b of the first additive in the non-aqueous electrolyte, and the mass percentage c of the second additive in the non-aqueous electrolyte is further defined to satisfy 3≤b+c≤8, 0.03≤b / c≤0.6, 2≤a / c≤1500, 10≤a≤5000, 0.1≤b≤2, and 2.5≤c≤6.5, which can improve the stability of the positive electrode active material of the battery and inhibit the impedance growth during high temperature cycling and storage.

[0089] It can be seen from the test results of Example 1 and Comparative Examples 1-18 that when any one of the parameters a of the total content of Ni and Mn elements in the positive electrode material layer, b of the mass percentage of the first additive in the non-aqueous electrolyte, and c of the mass percentage of the second additive in the non-aqueous electrolyte does not meet the range or the value of any one of the relationship equations b+c, b / c, and a / c is too large or too small, the lithium-ion battery cannot have good high temperature performance and low impedance growth, indicating that the total content a of Ni and Mn elements in the positive electrode material layer, b of the mass percentage of the first additive in the non-aqueous electrolyte, and c of the mass percentage of the second additive in the non-aqueous electrolyte have a strong correlation in improving the high temperature performance of the lithium-ion battery and inhibiting impedance growth.

[0090] Table 2 shows the test results of Example 7 and Examples 23-32; the difference between Examples 23-32 and Example 7 lies in the relevant parameters in Table 2.

[0091] Table 2

[0092]

[0093]

[0094] It can be seen from the test results in Table 2 that when the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage b of the first additive in the non-aqueous electrolyte, and the mass percentage c of the second additive in the non-aqueous electrolyte meet the relevant requirements, and further when the porosity ε of the positive electrode material layer and the relationship b / ε between the content of the first additive and the porosity satisfy 10≤ε≤40, 0.01≤b / ε≤0.2, the high temperature performance of the lithium-ion battery can be further improved and the impedance growth can be suppressed.

[0095] Table 3 shows the test results of Example 7 and Examples 33-46; the difference between Examples 33-46 and Example 7 lies in the relevant parameters in Table 3.

[0096] Table 3

[0097]

[0098]

[0099] It can be seen from the test results in Table 3 that when the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage b of the first additive in the non-aqueous electrolyte, and the mass percentage c of the second additive in the non-aqueous electrolyte meet the relevant requirements, further adding the third additive, and at the same time the mass percentage of the third additive satisfies 1≤d≤10, 0.1≤d / (b+c)≤2.5, it helps to improve the initial impedance of the battery under high energy density and further optimize the high temperature performance and impedance performance of the battery.

[0100] Table 4 shows the test results of Example 7 and Examples 47-54; the differences between Examples 47-54 and Example 7 lie in the relevant parameters in Table 4.

[0101] Table 4

[0102]

[0103] It can be seen from the test results in Table 4 that when the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage b of the first additive in the non-aqueous electrolyte, and the mass percentage c of the second additive in the non-aqueous electrolyte meet the relevant requirements, adding different types of first additives and different types of second additives can optimize the high temperature performance and impedance performance of the lithium-ion battery, indicating that the battery system of the present invention is universal for different types of first additives and different types of second additives.

[0104] Table 5 shows the test results of Example 32 and Examples 55-57; the differences between Examples 55-57 and Example 32 lie in the relevant parameters in Table 5.

[0105] Table 5

[0106]

[0107] It can be seen from the test results in Table 5 that when the total content a of Ni and Mn elements in the positive electrode material layer, the mass percentage b of the first additive in the non-aqueous electrolyte, the mass percentage c of the second additive in the non-aqueous electrolyte, and the mass percentage d of the third additive in the non-aqueous electrolyte meet the relevant requirements, adding different types of third additives can optimize the high temperature performance and impedance performance of lithium-ion batteries, indicating that the battery system of the present invention is universal for different types of third additives.

[0108] Table 6 shows the test results of Example 1 and Comparative Examples 19-22; the difference between Comparative Examples 19-22 and Example 1 lies in the relevant parameters in Table 6.

[0109] Table 6

[0110]

[0111]

[0112] It can be seen from the test results in Table 6 that the present invention, by doping at least one metal element of Ni or Mn in the positive electrode material layer, is more helpful in improving the activity and electrochemical properties of the lithium cobalt oxide positive electrode material than other doping elements, so that the prepared lithium ion battery has better high temperature performance and resistance to impedance growth.

[0113] The present invention is further described above with the aid of specific embodiments. However, it should be understood that the specific description here should not be construed as limiting the essence and scope of the present invention. Various modifications made to the above embodiments by ordinary technicians in the field after reading this specification are all within the scope of protection of the present invention.

Claims

1. A lithium ion battery, characterized in that: Including positive electrode sheet, negative electrode sheet, and non-aqueous electrolyte; The positive electrode plate includes a positive electrode material layer containing a positive electrode active material, wherein the positive electrode active material includes lithium cobalt oxide containing at least one metal element of Ni or Mn; The non-aqueous electrolyte comprises a lithium salt, an organic solvent and an additive; The additives include a first additive and a second additive, wherein the first additive includes at least one of the following compounds: The second additive includes a nitrile compound; The lithium-ion battery meets the following conditions: 3≤b+c≤8, 0.03≤b / c≤0.6, 2≤a / c≤1500, 10≤a≤5000, 0.1≤b≤2, 2.5≤c≤6.5; Wherein, a is the total content of Ni and Mn elements in the positive electrode material layer, in ppm; b% is the mass percentage of the first additive in the non-aqueous electrolyte, in %; c% is the mass percentage of the second additive in the non-aqueous electrolyte, in %.

2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery meets the following conditions: 3.5≤b+c≤7, 0.05≤b / c≤0.5, 12.5≤a / c≤750.

3. The lithium-ion battery according to claim 1, characterized in that The total content a of Ni and Mn elements in the positive electrode material layer is 100 ppm to 3000 ppm; and / or, The mass percentage b% of the first additive in the non-aqueous electrolyte is 0.3% to 1.5%; and / or, The mass percentage c% of the second additive in the non-aqueous electrolyte is 4% to 6%.

4. The lithium-ion battery according to claim 1, characterized in that: The nitrile compound includes at least one of succinonitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrinitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebaconitrile.

5. The lithium-ion battery according to claim 1, characterized in that: The porosity ε% of the positive electrode material layer meets 10% to 40%.

6. The lithium-ion battery according to claim 5, characterized in that: The porosity ε% of the positive electrode material layer and the mass percentage b% of the first additive in the non-aqueous electrolyte satisfy 0.01≤b / ε≤0.

2.

7. The lithium-ion battery according to claim 1, characterized in that: The non-aqueous electrolyte further includes a third additive, and the third additive includes at least one of fluorobenzene, 1,3,5-trifluorobenzene, 1,4-difluorobenzene, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

8. The lithium-ion battery according to claim 7, characterized in that: The mass percentage d% of the third additive in the non-aqueous electrolyte is 1% to 10%.

9. The lithium-ion battery according to claim 8, characterized in that: The mass percentage b of the first additive, the mass percentage c of the second additive, and the mass percentage d of the third additive satisfy 0.1≤d / (b+c)≤2.

5.

10. The lithium ion battery according to claim 9, characterized in that: The mass percentage b of the first additive, the mass percentage c of the second additive, and the mass percentage d of the third additive satisfy 0.2≤d / (b+c)≤1.5.

Citation Information

Patent Citations

  • Lithium ion battery

    CN114094109A

  • Lithium ion battery

    CN115117452A

  • Lithium ion battery

    CN115692825A

  • Lithium ion battery

    CN117790905A

  • Electrolyte and lithium ion battery

    CN118738559A